2021
DOI: 10.1177/07356331211017793
|View full text |Cite
|
Sign up to set email alerts
|

Active Learning by Visual Programming: Pedagogical Perspectives of Instructivist and Constructivist Code Teachers and Their Implications on Actual Teaching Strategies and Students’ Programming Artifacts

Abstract: The integration of visual programming in early formal education has been found to promote computational thinking of students. Teachers' intuitive perspectives about optimal learning processes – "folk psychology" – impact their perspectives about teaching "folk pedagogy" and play a significant role in integrating educational technologies, such as visual programming, within the formal curriculum. This study was conducted based on the mixed method research paradigm. First, a folk pedagogy questionnaire was distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
3
7
0
1
Order By: Relevance
“…However, the experimental group showed outstanding coding skills within the scope of the study with a total MPS of 94.32% (outstanding). The study results align with many other studies especially the ones of [17,18,19,20,21,22,23,24,25].…”
Section: Experimental Study Resultssupporting
confidence: 91%
“…However, the experimental group showed outstanding coding skills within the scope of the study with a total MPS of 94.32% (outstanding). The study results align with many other studies especially the ones of [17,18,19,20,21,22,23,24,25].…”
Section: Experimental Study Resultssupporting
confidence: 91%
“…In discussing teaching-learning-assessment in technologyenhanced K-12 environments, a more recent studies (Hadad et al, 2020;Kesler et al, 2022;Yondler et al, 2018;Yondler & Blau, 2021) revealed four prototypes of teachers that reflect their degree of centrality in the classroom: (1) the teacher as a sage-on-the-stage, (2) a facilitator, (3) a guide-on-the-side, and (4) a partner. Sage-on-thestage refers to a teacher prototype, which is dominant in the learning processes and characterized by a belief that teachers must provide students with clear direct instructions and determine learning activities, with little room for learners' independence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, the research showed that instructors who adopted student‐centered teaching practices were also found to be more inclined to integrate technology into their instruction (Kale & Goh, 2014; Ruggiero & Mong, 2015). Studies have also demonstrated that teachers adopt different teaching types in integration of technologies in learning environments (Kesler et al, 2022; Prescott, 2014; Quitadamo & Brown, 2001; Weaver & Nilson, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Ressalta-se que 47 estudos (40,5%) não fizeram menção às habilidades do PC. Um estudo fez uma pesquisa envolvendo 89 professores do Ensino Fundamental e Médio e buscou identificar de que forma as estratégias pedagógicas construtivistas e instrutivistas refletemse nos artefatos elaborados pelos alunos [27]. As tarefas foram realizadas utilizando a programação visual com o Scratch, onde foram experimentadas as habilidades do PC de abstração, decomposição, pensamento algorítmico, avaliação e a generalização.…”
Section: Conceitos E Habilidades De Pcunclassified
“…Esand Jeuring[63], Franklin et al[22], Salac et al[56], Troiano et al[62], Ng and Cui[40], Mukasheva and Omirzakova[37], Salac et al[55], Grizioti and Kynigos[23], Butler and Leahy[10], Jiang and Wong[25], Kesler et al[27], Morales-Urrutia et al[35], Wong and Cheung[69], Saxena et al[58], Rijke et al[52], Borges et al[7], Pellas and Peroutseas[46];(2) Mediano: Fowler et al[21], Kesselbacher and Bollin[28],Petrie[48], Repenning and Basawapatna[51], Mladenović et al[33], Monteiro et al[34], Piedade et al[50], Chongo et al[12], Díaz-Lauzurica and Moreno-Salinas[17], Grover et al[24], Sáez-López et al[53]; (3) Superficial: Feldhausen et al[18], Merkouris and Chorianopoulos[31], Clarke-Midura et al[13].…”
mentioning
confidence: 99%